Multimicronutrient supplementation and asymptomatic urinary tract infections in the elderly - Boekitwetan, Paul; Surjawidjaja, Julius E.; Aidilfit, Mahyunis; Lesmana, Murad (Faculty of Medicine, Trisakti University, 2009)
As human life expectancy continues to increase, developing countries are reporting higher percentages of elderly in their respective populations. The defense mechanisms of the elderly are reduced due to several factors, such as increased susceptibility to infection, specifically urinary tract infection (UTI). A randomised, placebo-controlled, double-blind trial was conducted to assess whether multimicronutrient supplementation is effective in reducing UTIs in older people in the community. A total of 261 elderly who lived in Mampang Prapatan district, South Jakarta, were randomised to daily multimicronutrient supplementation or control groups. The primary outcomes were the incidence of asymptomatic UTI, the organisms responsible for UTIs and the results of sensitivity tests on UTI microorganisms. UTI was defined as culture-positive urine yielding a single species of organisms in numbers greater than 104 cfu/mL urine specimen. At base-line 19.5% of the elderly had UTI, namely 23.7% patients in the MMN group and 16.7% in the control group, but the difference was not statistically significant (p=0.158). Escherichia coli was the most common microorganism, isolated in 20.7% of the MMN group and 17.5% of the control group. After six months of supplementation, UTI in the MMN group decreased by 40.6% compared with only 14.4% in the control group. The numbers of E. coli also declined by 64.3% in the MMN group compared to 37.8% in the control group. This study has confirmed the beneficial effect of multimicronutrient supplementation on UTI in the elderly.